2022
DOI: 10.4062/biomolther.2022.074
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Hyaluronic Acid Synthase-2 Mediate NRF2-Driven Chemoresistance in Breast Cancer Cells

Abstract: Hyaluronic acid (HA), a ligand of CD44, accumulates in some types of tumors and is responsible for tumor progression. The nuclear factor erythroid 2-like 2 (NRF2) regulates cytoprotective genes and drug transporters, which promotes therapy resistance in tumors. Previously, we showed that high levels of CD44 are associated with NRF2 activation in cancer stem like-cells. Herein, we demonstrate that HA production was increased in doxorubicin-resistant breast cancer MCF7 cells (MCF7-DR) via the upregulation of HA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Treatment with HA activates Nrf2 and induces Nrf2-target genes in bovine chondrocytes and human breast cancer cells, with increased phosphorylation of AKT or higher levels of p62, which competes with Nrf2 for binding to Keap1 (Komatsu et al, 2010), correlating with Nrf2 activation (Choi et al, 2022;Onodera et al, 2015;Ryoo et al, 2018). In addition, a hydrogel formulation of HA increased the levels of Nrf2 in frostbite-wounded skin tissues of Wistar rats (Joshi et al, 2021).…”
Section: Hyaluronic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with HA activates Nrf2 and induces Nrf2-target genes in bovine chondrocytes and human breast cancer cells, with increased phosphorylation of AKT or higher levels of p62, which competes with Nrf2 for binding to Keap1 (Komatsu et al, 2010), correlating with Nrf2 activation (Choi et al, 2022;Onodera et al, 2015;Ryoo et al, 2018). In addition, a hydrogel formulation of HA increased the levels of Nrf2 in frostbite-wounded skin tissues of Wistar rats (Joshi et al, 2021).…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…However, it was recently shown that ovarian cancer cell-derived high molecular-weight HA drives cholesterol efflux and depletion of lipid rafts from macrophages, which in turn drives IL-4 signaling and inhibition of IFNγ-induced gene expression ( Goossens et al, 2019 ). Treatment with HA activates Nrf2 and induces Nrf2-target genes in bovine chondrocytes and human breast cancer cells, with increased phosphorylation of AKT or higher levels of p62, which competes with Nrf2 for binding to Keap1 ( Komatsu et al, 2010 ), correlating with Nrf2 activation ( Choi et al, 2022 ; Onodera et al, 2015 ; Ryoo et al, 2018 ). In addition, a hydrogel formulation of HA increased the levels of Nrf2 in frostbite-wounded skin tissues of Wistar rats ( Joshi et al, 2021 ).…”
Section: Endogenous Nrf2 Activators In the Tumor Immune Microenvironmentmentioning
confidence: 99%
“…In MCF-7 drug-resistant BC cells, an increase in HA production was observed due to the upregulation of HA synthase-2 (HAS2), while the upregulation of HAS2 contributed to the chemoresistance of cancer cells, as well as their ability to form drug-resistant spheres, through activation of the CD44/Nrf2 signaling pathway [75]. HAS2 levels were also correlated with the malignant phenotype of BC cells [53].…”
Section: Breast Cancermentioning
confidence: 99%
“…Moreover, LOC101110341 (HAS2) is involved in synthesis of hyaluronan, which is associated with mammary growth during gestation (Tolg et al, 2017). The latter gene along with ZHX2, DERL1, FAM83A and ATAD2 have been associated with intense symptoms, resistance to chemotherapy and bad prognosis of human breast cancer and metastatic canine mammary adenocarcinomas, implying interference in mammary cell growth and immune regulation (Kalashnikova et al, 2010;Klopfleisch et al, 2010;Lee et al, 2012;Fang et al, 2021;Choi et al, 2022). In accordance with the above, the suggestive significant SNP rs428540973 on chromosome 12, which was associated with SCC in Frizarta sheep, is located within RBP7; downregulation of its expression in human breast cancer has been associated with bad prognosis (Lin et al, 2022).…”
Section: Genome-wide Association Study and Gene Annotationmentioning
confidence: 99%